Enhancer of Shoot Regeneration 2 (ESR2) regulates pollen maturation and vitality in watermelon (Citrullus lanatus) - Hu Wang; Lihong Cao; Yalu Guo; Zheng Li; Huanhuan Niu (Journal of Integrative Agriculture, 2024)
Watermelon (Citrullus lanatus) holds global significance as a fruit with high economic and nutritional value. Exploring the regulatory network of watermelon male reproductive development is crucial for developing male sterile materials and facilitating cross-breeding. Despite its importance, there is a lack of research on the regulation mechanism of male reproductive development in watermelon. In this study, we identified that ClESR2, a VIIIb subclass member in the APETALA2/Ethylene Responsive Factor (AP2/ERF) superfamily, was a key factor in pollen development. RNA in situ hybridization confirmed significant ClESR2 expression in the tapetum and pollen during the later stage of anther development. The pollens of transgenic plants showed major defects in morphology and vitality at the late development stage. The RNA-seq and protein interaction assay confirmed that ClESR2 regulates pollen morphology and fertility by interacting with key genes involved in pollen development at both transcriptional and protein levels. These suggest that Enhancer of Shoot Regeneration 2 (ESR2) plays an important role in pollen maturation and vitality. This study helps understand the male reproductive development of watermelon, providing a theoretical foundation for developing male sterile materials.